ANALISIS KEPUASAN KONSUMEN DALAM PENGURUSAN LABELISASI DAN SERTIFIKASI BENIH DI UPTD PPSBTPHP PROVINSI BENGKULU - Meliyana; Elni Mutmainnah; Anton Feriady; Edy Marwan; Rita Feni (Jurnal AGRIBIS, 2023)
This study aims to determine the analysis of consumer satisfaction in the management of seed labeling and certification in UPTD PPSBTPHP Bengkulu Province. The method used in this research is the census method. Respondents in this study were all parties, including seed farmers, farmer groups, private business entities, and government agencies who had managed seed labeling and certification at the UPTD PPSBTPHP Bengkulu Province in 2021, totaling 58 people. The analysis method is carried out by measuring the IKM or Community Satisfaction Index based on KEPMENPAN RB No. 14 of 2017 which consists of 9 indicators, namely (1) requirements (2) systems, mechanisms and service procedures (3) completion time (4) costs/tariffs ( 5) product specifications for the type of service (6) implementing competence (7) implementing behavior (8) handling complaints, suggestions and inputs (9) facilities and infrastructure. From the results of the study, it was found that the conversion value of the Community Satisfaction Index was 77.99 with a service quality of "B" category "Good / Agree", this indicates that consumers feel "Satisfied" with the services provided by UPTD PPSBTPHP Bengkulu Province. Keywords : Consumer Satisfaction Index, Seed Certification and Labeling.